2008
DOI: 10.1016/j.ejphar.2008.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of bisphosphonates and advanced glycation end-products on osteoblastic cells

Abstract: Patients with long-standing Diabetes mellitus can develop osteopenia and osteoporosis. We have previously shown that advanced glycation endproducts reduce the bone-forming activity of osteoblasts. Bisphosphonates are used for the treatment of various bone disorders, since they reduce osteoclastic function and survival, and stimulate osteoblastic bone-forming capacity. In this work we have investigated whether bisphosphonates are able to revert advanced glycation endproducts-induced deleterious effects in osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 38 publications
5
48
1
11
Order By: Relevance
“…Thus the statistical significance which was only found at 48 hours represents an isolated piece of information and does not modify the results observed in the study. Stability with the formation of calcium nodules was nondescript for the administration of the drug, in agreement with the reports by Gangoiti et al 5 , Graham et al 2 , Dane et al 3 , Qiu et al 6 and Ferrari et al 7 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus the statistical significance which was only found at 48 hours represents an isolated piece of information and does not modify the results observed in the study. Stability with the formation of calcium nodules was nondescript for the administration of the drug, in agreement with the reports by Gangoiti et al 5 , Graham et al 2 , Dane et al 3 , Qiu et al 6 and Ferrari et al 7 .…”
Section: Discussionsupporting
confidence: 91%
“…This demonstrates that this drug apparently does not possess cytotoxic action nor does it interfere with cell proliferation. Gangoiti et al 5 obtained similar results to this study using the same type of MC3T3 cells and bisphosphonates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…AGEs-modified bovine serum albumin was prepared by incubation of 10 mg/ml bovine serum albumin (BSA) with 33 mM d-glycolaldehyde in 150 mM phosphate-buffered saline pH 7.4 at 37 • C for 3 days under sterile conditions, as previously described (Gangoiti et al, 2008). d-Glycolaldehyde was used as the glycating sugar instead of glucose to speed up non-enzymatic glycosylation.…”
Section: Preparation Of Advanced Glycation Endproductsmentioning
confidence: 99%
“…In a recent study we showed that low doses (10 −8 M) of BP completely prevented the AGEs-induced alterations in osteoblast proliferation, differentiation, apoptosis and reactive oxygen species production (Gangoiti et al, 2008). However, high doses of BP (10 −4 -10 −5 M) were toxic for osteoblasts.…”
Section: Introductionmentioning
confidence: 96%